PROFIL PROTEIN IKAN LEMURU DENGAN PENGERINGAN OVEN, PENGERING MATAHARI DAN SINAR MATAHARI BERBASIS SDS PAGE - Singapurwa, Ni Made Ayu Suardani; Candra, I Putu; Semariyani, A.A. Made (Jurnal Teknologi Hasil Pertanian, 2022)
Lemuru fish (Sardinella lemuru) contains high nutritional value and is very important for humans as well as affordable source of protein. Lemuru fish are very perishable and seasonally produced, so it needs to be preserved. The people of Jembrana Regency, Bali, preserve it into spiced dried fish called Pedetan. The aim of this study was to determine the protein profile of unseasoned and seasoned lemuru fish which were dried in an oven, artificial dryer and sun drying. The research method used is the Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) method to determine the molecular weight (BM), to see the damage to the protein in the sample. The results of analysis of the protein profile of lemuru meat based on its molecular weight using SDS-PAGE showed that the molecular weight of the separated protein bands varied from 31 to 524 kDa. Based on the results of protein profile analysis, sun drying can cause protein denaturation which is characterized by a decrease in the number of protein bands. Drying with an artificial drying device can reduce damage, because the protein bands can still be maintained, and drying with an oven causes protein damage that is not as big as drying with the sun drying method. While the addition of seasoning for fresh lemuru does not cause protein damage, it can be seen from the number of protein bands that do not change.